A epistemologia genética de Jean Piaget e suas contribuições para a formação de professores - Oliveira, Fábio Pereira de (Universidade Federal do Tocantins, 2021)
This monograph aims to discuss the central concepts of the theory developed by Jean William Fritz Piaget, known as Genetic Epistemology, from the perspective of intellectual cognitive development of the subject. The research presents the stages of intellectual cognitive development and their specificities, as well as the processes of formation of cognitive structures described by the theory of equilibrium. Piaget explains, through the concepts of assimilation, accommodation and equilibrium, the interactions of the subject with the object, obtaining as a product of this relationship the construction of knowledge. Based on this theory, formative experiences are presented during internship and academic monitoring curriculum activities. It is necessary to consider the relevance of the theme researched here, being to the future educators the important contribution of this theoretical reference for the strengthening of their formation and professional qualification.